EFEKTIVITAS PROGRAM PEMBAGIAN LIMA RIBU MASKER DESA PESANGGRAHAN KOTA BATU - Frydi Dimas Mahendra; Arie Ambarwati; Wildan Taufik Raharja (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
The Indonesian government itself has designated Covid-19 as a National Disaster According to Presidential Decree no. 12 of 2020 (2020) which states Covid-19 as a non-natural disaster that has had an impact on increasing the number of victims and property losses, the Pesanggrahan Village Batu City itself has a work program when in During this pandemic period, namely a program of five thousand masks that were distributed to the community in Pesanggrahan Village, this program was carried out in accordance with the Circular Letter of the Village Minister Number: S.2294/HM.01.03/VIII/2020 (2020) aimed at making the community especially in Pesanggrahan Village obedient in carrying out health protocols and carrying out the role of the village in controlling covid-19 in rural communities, so that the Pesanggrahan village can realize a Covid-19 Safe Village. Descriptive quantitative research is the main method used for investigation after studying the considerations of the purpose of investigation and investigation. The analytical technique used in this research is descriptive statistics using data classification using class interval method. The research on the mask distribution program on the variables used by the program is still not effective because the program monitoring variable gets a value of 64% of the community assessing that the masks distributed are not all residents get masks, only the Head of the Family gets 1 mask.